PENGARUH PELATIHAN DAN SUPERVISI TERHADAP KEDISIPLINAN KERJA DAN DAMPAKNYA PADA PRESTASI KERJA PEGAWAI NEGERI SIPIL - Oktaliani, Metha (Universitas muhammadiyah palembang, 2017)
This study was conducted to know the effect of training and supervision and work discipline on the performance of civil servants in SKPD Social Agency of South Sumatra province. Methodology design using primary data and data secondary. Sampling Probability sampling methods that amounted to 133 employees with technique of data collection through questionnaires. In this research model test is test multicollinearity and heteroscedasticity test, and test koefesien include F test and t test after it conducted the analysis model lines (direct and indirect influence). The result, simultaneously all variables are variables of training, supervision and discipline of work only to have influence on work performance by 38.3% while 61.7% influenced by other variables that are not addressed in this study, while partially only variable that was significantly training no effect on job performance with the magnitude of -0.148.